2020
DOI: 10.1021/acs.analchem.9b04377
|View full text |Cite
|
Sign up to set email alerts
|

Trace Analysis of 61 Emerging Br-, Cl-, and I-DBPs: New Methods to Achieve Part-Per-Trillion Quantification in Drinking Water

Abstract: Disinfection byproducts (DBPs) are a ubiquitous source of chemical exposure in drinking water and have been associated with serious health impacts in human epidemiologic studies. While toxicology studies have pinpointed DBPs with the greatest toxic potency, analytical methods have been lacking for quantifying complete classes of most toxic DBPs at sufficiently low quantification limits (ng/L). This new method reports the parts-per-trillion quantification for 61 toxicologically significant DBPs from 7 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 45 publications
(80 reference statements)
1
75
1
Order By: Relevance
“…For the 0.5 h chlorinated water sample, the percent recoveries of TOCl and TOBr with multiple LLE (53% and 54%) were significantly higher than those with single LLE (25% and 27%). Particularly, multiple LLE has been reported to achieve relatively high recoveries for hydrophilic halo-DBPs with low K ow values. , Therefore, multiple LLE was selected as the pretreatment method for the chlorinated water samples prior to the UPLC separation and toxicity bioassay. Notably, freeze-drying, nitrogen purging, and rotoevaporation were not selected for sample pretreatment because they would generate a chlorinated sample concentrate rich in inorganic salts, which is not compatible with the UPLC/ESI-tqMS analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the 0.5 h chlorinated water sample, the percent recoveries of TOCl and TOBr with multiple LLE (53% and 54%) were significantly higher than those with single LLE (25% and 27%). Particularly, multiple LLE has been reported to achieve relatively high recoveries for hydrophilic halo-DBPs with low K ow values. , Therefore, multiple LLE was selected as the pretreatment method for the chlorinated water samples prior to the UPLC separation and toxicity bioassay. Notably, freeze-drying, nitrogen purging, and rotoevaporation were not selected for sample pretreatment because they would generate a chlorinated sample concentrate rich in inorganic salts, which is not compatible with the UPLC/ESI-tqMS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Single liquid–liquid extraction (LLE) is frequently used in chemical and biological analyses of DBPs. , Recent studies have demonstrated that multiple LLE increased the extraction recoveries of various halo-DBPs in disinfected waters compared with the commonly used single LLE , and solid-phase extraction . Thus, the extraction efficiency of multiple LLE with methyl tert -butyl ether (MtBE) was evaluated using a 0.5 h chlorinated water sample as a representative.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, more than 700 DBPs have been identified in drinking water, and many are cytotoxic, genotoxic, mutagenic, or carcinogenic. , Among these compounds, iodo-THMs (I-THMs), iodoacetic acids (IAAs), haloacetonitriles (HANs), haloacetaldehydes (HALs), halonitromethanes (HNMs), halo­acetamides (HAMs), and haloketones (HKs) are considered as priority DBPs, owing to their detection frequency, concentrations, and toxicities. Compared to regulated THMs and haloacetic acids (HAAs), most of these unregulated priority DBPs are much more cytotoxic and genotoxic. , However, there is little information on the occurrence and formation of DBPs in tea, with only one paper reporting one class of DBPs (THMs) in tea brewed using real tap water …”
Section: Introductionmentioning
confidence: 99%
“…Each SPE cartridge was conditioned using 10 mL of MtBE or EtOAc followed by 10 mL of methanol and then equilibrated using ≥10 mL of DI water. Prior to the extraction, the NaHCO 3 solution spiked with test compounds was acidified to pH ∼3.7 using H 2 SO 4 ; this pH value was chosen because we expected the extraction to take hours, and unregulated (semi-)­volatile DBPs have been shown to be stable around pH 3.7. , We did not conduct SPE at the same pH as XAD resin extraction because high background toxicity can result from leaching from surface-modified styrene divinylbenzene sorbents at pH <2; degradation of other types of SPE sorbents has also been observed at low pH. , Afterward, the solution was loaded onto the SPE cartridge using vacuum at a flow rate of 7 mL/min. After the extraction finished, the SPE cartridge was dried under vacuum for 2 min before eluting with 15 mL of MtBE or EtOAc; this elution targeted the Sepra ZTL sorbent.…”
Section: Materials and Methodsmentioning
confidence: 99%